Rare bird documentation form for Northern Goshawk at Big Creek Lake, 1983 - Bray, Tanyaet al; Rose, B.J.et al; Bray, Donet al; Rose, Sharonet al (1983)
Rare bird documentation form for a Northern Goshawk at Big Creek Lake in Polk County, IA on January 15, 1983. Epson - sheet feed/flatbed